2014
DOI: 10.1186/1755-8794-7-39
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chiari Type I Malformation subtypes using whole genome expression profiles and cranial base morphometrics

Abstract: BackgroundChiari Type I Malformation (CMI) is characterized by herniation of the cerebellar tonsils through the foramen magnum at the base of the skull, resulting in significant neurologic morbidity. As CMI patients display a high degree of clinical variability and multiple mechanisms have been proposed for tonsillar herniation, it is hypothesized that this heterogeneous disorder is due to multiple genetic and environmental factors. The purpose of the present study was to gain a better understanding of what fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…For example, a familial group of Griffon Bruxellois, with a rounded cerebellum (CM0), had ventriculomegaly, heighted cranial fossa and SM indicating disruption of CSF flow ( 29 ). Similarly, the description of Chiari malformation in humans has morphed over time and includes CM Type 0 with normally placed cerebellar tonsils ( 21 , 30 ). The human classification of SM has also changed over time ( 25 , 31 ) with advanced imaging techniques applied to CSF circulation and it is possible that further phenotypic variations for both SM and CM may be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a familial group of Griffon Bruxellois, with a rounded cerebellum (CM0), had ventriculomegaly, heighted cranial fossa and SM indicating disruption of CSF flow ( 29 ). Similarly, the description of Chiari malformation in humans has morphed over time and includes CM Type 0 with normally placed cerebellar tonsils ( 21 , 30 ). The human classification of SM has also changed over time ( 25 , 31 ) with advanced imaging techniques applied to CSF circulation and it is possible that further phenotypic variations for both SM and CM may be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In a set of 2 publications, Markunas et al 9,10 examined the relationship between cranial base morphometrics and whole-genome expression profiles, finding that much posterior fossa morphology was heritable. Multiple genomic regions were strongly implicated with posterior fossa morphology using ordered subset analysis, including chromosomes 1 and 22.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have identified genes involved in chondrogenesis, such as EP3000 , CREBBP , SOX9 , ATF4 and LHX4. 45 A limited number of case reports have presented the association of this condition with abnormal skull morphology, especially due to a small posterior fossa in the context of bone disorders such as X-linked recessive hypophosphatemic rickets (OMIM #300554), or its X-linked dominant counterpart (OMIM # 307800). 46,47 However, a clear mechanistic association between these conditions has not been accomplished.…”
Section: Discussionmentioning
confidence: 99%